Indonesian Islamic Women Movement (A Case Study of BKSWI West Java) - Masripah Masripah (International Journal of Nusantara Islam, 2013)
This article discusses the women's movement in the organization BKSWI Indonesia Islam (Islam Women Cooperation Agency) West Java. Discussion of the methodology used is descriptive qualitative analysis. The conclusion based on the results of the discussion that: BKSWI can be assumed as the activities pursued women and can strengthen the organization by emphasizing equality and togetherness with me aim materialized unity among Islamic women's organizations as well as the implementation of Islamic teachings in increasing the degree and character of women in the life personal, household, and community are blessed by God, in order to realize the potential of the field of religious struggles of womanhood and society in me run that purpose, the HR (caretaker), facilities and funding access, information, culture management organizations, internal and external communications, leadership, organizational environment conducive Islamic women.